GORMON PEPTIDLAR, ULARNING BIOLOGIK VAZIFALARI VA MOLEKULASINING TUZILISHI - Qodirova, Zulfiya (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This article provides information about peptide hormones, their chemical formulas determined by scientists, as well as their biological roles.